Incidence and determinants of excessive weight gain in people living with HIV initiating tenofovir, lamivudine, and dolutegravir-based therapy: a multicenter retrospective study in northwest Ethiopia - Chanie, Gashaw Sisay; Atalay, Wagaye; Zeleke, Tirsit Ketsela; Bayleyegn, Zemenu Wube; Aragie, Yonas Sisay; Bizuneh, Gizachew Kassahun; Melese, Mihret; Abebe, Rahel Belete (Frontiers in Pharmacology, 2025)
BackgroundThe incidence and nature of excessive weight gain associated with antiretroviral treatment using tenofovir, lamivudine, and dolutegravir based regimens among patients living with human immunodeficiency virus has not been properly examined in Ethiopia. Therefore, this study aimed to assess the incidence and factors associated with excessive weight gain among People living with human immunodeficiency virus on tenofovir, lamivudine, and dolutegravir based regimens in a real-world setting.MethodA multicenter retrospective cross-sectional study was conducted from December 1, 2022, to August 30, 2023, involving 620 human immunodeficiency virus patients initiating a tenofovir, lamivudine, and dolutegravir based regimen. Data on sociodemographic, clinical details, and excessive weight gain were collected from medical records and patient interviews using a semi-structured questionnaire. Continuous variables were reported with mean and standard deviation. Binary logistic regression analysis was performed, and variables with a P-value ≤0.25 were included in multivariate logistic regression. Statistical significance was set at a P-value of ≤0.05.ResultsA total of 620 participants were involved in the analysis, revealing a 31.43% incidence of excessive weight gain 95%CI (27.1–36.0). The mean weight gain was 3.77 kg with a 1.5 SD at 72 months follow-up. Factors such as being female [AOR = 1.75, 95% CI (1.01, 3.04)], age between 38–46 years [AOR = 1.53, 95% CI (1.23, 2.76)], lack of physical activity were [AOR = 4.41, 95% CI (1.46, 11.80)], having 6–12 months and 13–24 months of since starting new regimen follow up duration [AOR = 3.35, 95% CI (2.79, 4.30)] and [AOR = 2.67, 95% CI (2.43, 3.25)] respectively and having detectable viral load at initiation of regimen [AOR = 2.34, 95% CI (1.18, 6.63)] were significantly associated with excessive weight gain.ConclusionPLHIV receiving a tenofovir, lamivudine, and dolutegravir based regimen particularly females, aged 38–54 years, those with limited physical activity, follow-up durations of 6–24 months, advanced disease stages, and a detectable viral load at therapy initiation should be closely monitored for weight gain. Proactive surveillance in these patient groups is crucial to optimize therapeutic outcomes and address potential health concerns associated with weight changes.